Eustachian valve endocarditis. Issue 4 (2nd October 2019) - Fan, Jerry; Le, Phuong Tram N.; Jones, Billy Don
Abstract: Eustachian valve infective endocarditis is rare and mostly affects intravenous drug abusers and those with implanted medical devices or indwelling central venous catheters. The most commonly identified organism is Staphylococcus aureus . Treatment includes intravenous antibiotics for approximately 6 weeks. We present a case of Staphylococcus aureus Eustachian valve endocarditis in an individual without traditional risk factors.